Lentas mudanças: o voto e a política tradicional - Lúcia Avelar; Maria Inez Machado Telles Walter (Opinião Pública)
O objetivo deste artigo é analisar a relação entre poder político e desenvolvimento, bem como avaliar as mudanças políticas nos municípios brasileiros. O estudo está baseado em dados do TSE para as eleições municipais de 1996, 2000 e 2004, e leva em conta variáveis estruturais como tamanho e qualidade de vida dos municípios (IBGE/IPEA/PNUD) e a ideologia dos partidos políticos. A conclusão é que os partidos tradicionais têm maior apoio nos municípios menores e com pior qualidade de vida. The goal of the present work is to analyze the relationship between development and political power, as well as to evaluate political changes in municipalities in Brazil. The study is based on a data bank from municipal elections (Tribunal Superior Eleitoral, 1996, 2000 and 2004) applying a procedure which takes structural variables into account, such as size and quality of life in municipalities (IBGE/IPEA/PNUD), and ideology of political parties. The question is whether favorable geographic-political configurations exist for left or right wing parties. Our conclusion is that traditional political parties (right wing) find larger support in micro municipalities with bad quality of life.